POLA KOMUNIKASI POKDARWIS PADA DAERAH WISATA AIR TERJUN TAMBAK LARE DI DESA KARE MADIUN JAWA TIMUR - Mochammad Firgiardiansyah; Jericho Michael Andrian (Universitas 17 Agustus 1945 Surabaya, 2023)
The Tourism Awareness Group or Pokdarwis of the Lare waterfall located in Kare Madiun village, East Java was formed to develop community groups in an effort to improve welfare in the economic field and have readiness and concern for tourism destinations so that they act as good hosts, tourism conscious movers and sapta charm in the effort to establish local tourism branding based on local wisdom (development of the natural, social and cultural potential of the local community). So that in the end, the existence of the Lare Waterfall tourist destination in the village of Kare Madiun, East Java, has a very high bargaining position compared to other tours. The purpose of this study was to determine the Communication Patterns of Tourism Awareness Groups (Pokdarwis) in Developing the Lare Waterfall in Kare Madiun Village, East Java. While in practice it uses descriptive qualitative research methods with data analysis techniques Miles and Huberman Models namely data reduction analysis activities, data display and conclusion drawing/verification. In addition, this study uses data validity techniques through source triangulation, namely comparing or re-checking the degree of trust in information obtained from different sources. As a result, it can be seen that the Pokdarwis communication pattern with the formation of all directions where individuals in all positions are enabled to send and receive information in all directions. This can be seen from the findings that the head of the Coconut Beach Pokdarwis always coordinates with all administrators, traders and visitors at the waterfall without exception and vice versa. So in sending messages and receiving messages in all directions, nothing is covered up, everything is open for the common interest in advancing tourism in the village of Kare Madiun by prioritizing uploads and local customs. In conclusion, the Pokdarwis waterfall in Lare village uses an all-way communication pattern so that communication can run effectively.